Rol del docente y su incidencia en aulas disfuncionales en los estudiantes de quinto año de EGB de la Unidad Educativa Emigdio Esparza Moreno, Babahoyo, 2022-2023 - Jimenez Olvera, Joice Jaritza (2023)
The role of the teacher significantly influences the learning process; since, his function is to facilitate knowledge to students, recognize and attend to their individual needs. Therefore, the main objective of this research is to determine how the role of the teacher affects dysfunctional classrooms in the students of the fifth year of basic education at the Emigdio Esparza Moreno Educational Unit, Babahoyo, 2022-2023.The methodology of this case has a mixed approach, because qualitative and quantitative data are obtained, while the type of research used was descriptive and explanatory. The population was made up of 150 students and 5 teachers belonging to the Emigdio Esparza Moreno Educational Unit and the sample was selected by means of a sampling at the convenience of the researcher where 30 students of fifth grade "A" and the 5 teachers belonging to the previously mentioned school level were selected. The technique used was the survey, which was directed to the 5 teachers and 30 students. The results obtained were that teachers are constantly trained to face educational challenges, but there is no proper management of educational resources, the lack of clear communication and the application of strategies for a pleasant coexistence in the classroom, influences the creation of dysfunctional classrooms, which hinders the work of teachers and prevents the student from obtaining meaningful learning, so it is necessary that teachers acquire skills to counteract these conflictive situations.